A green method for preparing mechanically robust poly(propylene carbonate) with full biodegradability via incorporating hybrid natural filler. Issue 19 (4th March 2023) - Zhang, Xuhui; Ji, Guangyao; Yang, Jianing; Jiang, Jie; He, Jianzhong; Li, Ting; Huang, Jing; Chen, Mingqing; Dong, Weifu
Abstract: Strong, tough, and biodegradable polymers from renewable raw materials are of great importance in circumventing environmental issues. Poly(propylene carbonate) (PPC), a biodegradable carbon dioxide (CO2 )/propylene oxide copolymer, has been simultaneously strengthened and toughened by incorporating a hybrid natural filler (CNF@xyl). The CNF@xyl is formed by coating cellulose nanofibril (CNF) with small xylitol (xyl) particles using evaporation‐induced self‐assembly. In CNF@xyl, the xyl cladding around CNF can improve the dispersion of CNF in PPC by inhibiting the contact among CNF, and can enhance the interfacial interaction by providing high‐density hydrogen bonds. Meanwhile, the CNF can minimize the size of xyl particles by being a substrate for xyl spreading. Consequently, by incorporating the hybrid fillers at small fraction, PPC/(CNF0.4@xyl2.0) exhibits a Young's modulus of 1318 ± 65 MPa, a tensile strength of 19.07 ± 0.98 MPa, and a toughness of 77.64 ± 3.21 MJ/m 3, which is 161%, 145%, and 130% of that of neat PPC, respectively. More importantly, CNF, xyl, and PPC are fully biodegradable while CNF and xyl are renewable. This work offers a novel yet green method for optimizing the mechanical properties of biodegradable polymers and provides an alternative way to circumvent environmental issues. Abstract : A hybrid natural filler that CNF is coated by xyl (CNF@xyl) successfully prepared using evaporation‐induced self‐assembly. The hybrid filler can disperse in PPC evenly by melt‐blending and can simultaneously strengthen and toughen PPC due to the optimized interfacial interaction and dispersion of fillers. This work offers a novel yet green method for optimizing the mechanical properties of biodegradable polymers and provides an alternative way to circumvent environmental issues.